Awareness of Phymill treatment for cerebral palsy kids among university students’ perspective - Ariffin, Rabiatul Aisyah; Mohd Hasni, Nur Hazreen; Mohd Adib, Mohd Azrul Hisham (Intelektual Pustaka Media Utama, 2024)
Cerebral palsy (CP) kids are a group of disorders that affect their mobility. This health condition is somewhat of a crucial disability and requires treatment to have a better lifestyle as they grow older. It is important to acknowledge the existence of this CP and ways to battle or treat it. Currently, the physio-treadmill (PhyMill) is well developed for CP kids. In this study, we focus on a quantitative survey that was conducted to predictors of the knowledge towards CP and PhyMill among university students, and to observe the awareness of the treatment based on ergonomics, biomechanics, and safety aspects using the PhyMill. The results showed that a huge percentage of students are aware of the knowledge of CP and how to know if an individual is experiencing this disability. The responses for the function of PhyMill have shown the students that the function of the PhyMill is to stimulate the conditioning of a healthier lifestyle in patients with this health condition. The responsive feedback of treatment on ergonomics, biomechanics, and safety aspects also shows comfortable, user-friendly, and good safety inventions by using PhyMill. The significance of this study is would explore the possibility of PhyMill to enhance the performance of patient treatment.